Childhood in the Late Ottoman Empire and After - Fortna, B.C (The Ottoman Empire and its Heritage, 2016)
This title, in its entirety, is available online in Open Access. This volume explores the ways childhood was experienced, lived and remembered in the late Ottoman Empire and its successor states in the late nineteenth and early twentieth centuries when rapid change placed unprecedented demands on the young.